Manajemen Anestesi Cedera Vertebra Cervical 4,5 dengan Tindakan Laminektomi Dekompresi Stabilisasi - Sudadi; Zaki, Wildan Arsyad; Rahardjo, Sri (Jurnal Komplikasi Anestesi, 2018)
Preoperative management of cervical fractures of particular concern include the level of injury, onset of occurrence and cardiorespiratory complications. Then continued the definitive management of laminectomy requiring inline position intubation positions, invasive arterial line monitors and CVC, durante vasoactive drug support in case of hemodynamic decline. Equally important is postoperative intensive care, and treatment of complications of pneumonia, DVT, sepsis due to long immobilization. Treatment of a 54-year-old male patient with a diagnosis of VC IV-V compression fracture, tetraplegi and increased transaminase enzyme. Patients were initially treated in HCU LOC 2 for 10 days with drug support and hemodynamic monitoring, then definitive elective laminectomy, decompression, stabilization. The operation lasted for approximately five hours with bleeding approximately 1200cc, urine output 2.5 cc / kgBW / hour. Post surgery patients treated in ICU with attached tracheostomy, connected with ventilator and vasoactive drug support. During treatment in ICU, hemodynamic monitoring with arterial line, ECG, pulse oximetry, temperature monitor and CVC were performed. Patients are positioned in line mobilization, ureter catheter installed and NGT. Hemodynamic, blood pressure during ICU ranged from syst 100-110 mmHg, diastole blood pressure 50-80 mmHg, pulse 90-110 x / minute and saturation 93-100%. With supportive therapy of ceftriaxone injection, methylprednisolone, fentanyl, mecobalamin, omeprazole, and dobutamine and norepinephrine continue. The patient was treated for 5 days and after stabilizing the patient was returned to the ward.